Whole exome sequencing analysis of Malaysian monozygotic twin suspected with primary immunodeficiency diseases / Hamidah Abdul Ghani - Hamidah , Abdul Ghani (2019)
Primary immunodeficiency diseases (PID) are rare genetic diseases with more than 200 different forms of PID sharing almost similar symptoms. A pair of female Malay descendant monozygotic twin (MZ twin) was presented with recurrent upper respiratory tract infections, bicytopenia associated hepatosplenomegaly, which the clinicians suspected with PID. However, the definite diagnosis was not clear due to the complexity of the disease phenotypes. Whole exome sequencing analysis was applied to identify the disease-causative gene mutations for this MZ twin. A total numbers of 84 and 81 millions of paired-end reads were received with 99.26% and 99.39% were mapped back to the human reference genome hg38. We identified a compound heterozygous case of CD21 gene at position c.1916G>A and c.2012G>A, suggesting that both patients had CD21 deficiency. The pathogenic missense mutation were confirmed using Sanger sequencing. The study revealed that both patients suffering common variable immunodeficiency (CVID) due to the deficiency in CD21 gene. We had also conducted gene network analysis for CD21 gene to understand the gene-gene relationship among the CVID-related genes.